All the doctrines of the Bible : a study and analysis of major Bible doctrines - Lockyer, Herbert, 1886- (Grand Rapids, MI : Zondervan, 1964)
Includes bibliographical references and index
Brethren writer.
Keywords: Theology, doctrinal